2022
DOI: 10.1097/sla.0000000000005715
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Total Mesorectal Excision

Abstract: Objective: Magnetic resonance imaging–based subdivision of the pelvis into 7 compartments has been proposed for pelvic exenteration. The aim of the present anatomical study was to describe the topographic anatomy of these compartments and define relevant landmarks and surgical dissection planes. Background: Pelvic anatomy as it relates to exenterative surgery is complex. Demonstration of the topographic peculiarities of the pelvis based on the operative situs is hindered by the inaccessibility of the small p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The study systematically approached the subject using seven compartments defined by magnetic resonance imaging, identifying crucial anatomical landmarks and key structures that facilitate pelvic exenterative surgery. [35] These compartments include the peritoneal reflection compartment, anterior compartments (above and below for both males and females), central compartment, lateral compartment, posterior compartment, and inferior compartment. It is important to note that beyond TME surgery is typically performed by highly specialized teams who possess a thorough understanding of pelvic compartments and the options and limitations of extended surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study systematically approached the subject using seven compartments defined by magnetic resonance imaging, identifying crucial anatomical landmarks and key structures that facilitate pelvic exenterative surgery. [35] These compartments include the peritoneal reflection compartment, anterior compartments (above and below for both males and females), central compartment, lateral compartment, posterior compartment, and inferior compartment. It is important to note that beyond TME surgery is typically performed by highly specialized teams who possess a thorough understanding of pelvic compartments and the options and limitations of extended surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Extenterative surgery represents the sole method for obtaining a tumor-free margin, extending beyond the principles of TME. The work of Stelzner et al [35] presented a pelvic compartment classification based on 13 formalin-fixed pelvis specimens. The study systematically approached the subject using seven compartments defined by magnetic resonance imaging, identifying crucial anatomical landmarks and key structures that facilitate pelvic exenterative surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For locoregional assessment, pelvic magnetic resonance imaging (MRI) has been the preferred imaging technique to determine the tumor size and invasion of surrounding tissues. Recently, MRI-based subdivision of the pelvis into seven compartments has been introduced for planning pelvic exenterations in colorectal cancer patients, reporting high sensitivity for locoregional tumor invasion [22,23]. Positron emission tomography-computed tomography (PET-CT) is the commonly used imaging modality for evaluating the presence of distant metastases.…”
Section: Of 15mentioning
confidence: 99%
“…In 2023, in Annals of Surgery, the compartment-based anatomy for colorectal cancer was revisited on the basis of MRI studies of 13 pelvic specimens from body donors, of which 6 females, and the anatomical landmarks for each compartment were described in detail [22]. Given that the original and revisited central compartment description for colorectal cancer contains the rectum and mesorectum as well as the pelvic autonomic nerves, the central compartment for persistent or recurrent cervical cancer should contain instead the uterus and cervix with its parametrium, the vagina with its paracolpium, the proximal round ligaments and the uterine/vaginal vessels.…”
Section: Compartment-based Imagingmentioning
confidence: 99%
“…Georgiou et al established an MRI staging system based on seven pelvic compartments and reported excellent results with respect to diagnostic performance [11]. Meanwhile, the usefulness of the proposed pelvic compartmentation was confirmed on an anatomical base [12].…”
Section: Introductionmentioning
confidence: 98%